Development Strategy of Coconut Sugar Household Industry in Suruh District - Prasetya, Muhammad Lutfi (Efficient: Indonesian Journal of Development Economics, 2020)
The purpose of this study are (1) To get knowledge of the profile on home industry of coconut sugar in Suruh District, Semarang Regency, (2) Analyze some problems which possible come from internal and external side of home industry of coconut sugar in Suruh District, Semarang Regency, (3) Analyze some strategy which can be implemented on home industry of coconut sugar in Suruh District, Semarang Regency. This Study used descriptive qualitative method. Data analysis used descriptive analysis and SWOT analysis. The result of this study showed that from internal factor the main strength is raw materials from their own only and the weakness is limited raw materials. From main external factor the opportunity is large market share and the threat is difficulty of regenerating human resources. The main alternative strategy is ST strategy (Strength-Threat). The alternative strategy as per matrix IE has been placed on V quadrant. Main strategy which can be implemented is developing with expand a new product, increase quality of the products or services, or increasing the access for the bigger market, also avoiding lost sale and lost profit. Coconut sugar industry can expand the market, facility of the production, and technology. According to SWOT quadrant diagram, the main formulation of alternative strategies used ST strategy, it used by utilizing the power to overcome the threats the coconut sugar home industry faces. Tujuan dari penelitian ini (1) Mendeskripsikan kondisi industri rumah tangga gula kelapa di Kecamatan Suruh Kabupaten Semarang, (2) Mengetahui faktor internal (kekuatan dan kelemahan) dan eksternal (peluang dan ancaman) bagi industri rumah tangga gula kelapa di Kecamatan Suruh Kabupaten Semarang, (3) Menyusun strategi pengembangan yang perlu dilakukan dalam mengembangkan industri rumah tangga gula kelapa di Kecamatan Suruh Kabupaten Semarang. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Analisis data menggunakan analisis deskriptif dan SWOT. Hasil penelitian menunjukkan bahwa faktor internal yang menjadi kekuatan utama adalah bahan baku milik sendiri dan yang menjadi kelemahan utama adalah keterbatasan bahan baku yang tersedia. Faktor eksternal yang menjadi peluang utama adalah pangsa pasar yang masih luas dan yang menjadi ancaman utama adalah regenerasi SDM sulit. Perumusan alternatif strategi berdasarkan matriks IE berada pada kuadran V. Strategi utama yang dapat dilakukan adalah penetrasi pasar dan pengambangan produk. Berdasarkan diagram kuadran SWOT, perumusan alternatif strategi yang paling utama adalah strategi ST (Strenghts-Threat), dengan cara memaanfaatkan kekuatan yang dimiliki untuk mengatasi ancaman yang dihadapi